Energetics of clouding and size effects in non-ionic surfactant mixtures: The influence of alkyl chain length and NaCl addition - Molina-Bolivar, Jose Antonio; Hierrezuelo-Osorio, José Manuel; Carnero-Ruiz, Cristóbal (Elsevier, 2012)
The clouding behavior of two non-ionic mixed surfactant systems (n-dodecyl-b-D-maltoside/n-dodecylhexaethylene-glycol and n-decyl-b-D-maltoside/n-dodecyl-hexaethylene-glycol) was investigated over the entire composition range in pure water and in 1 M NaCl. The evolution of micellar size as a function of temperature was monitored by dynamic light scattering and a unimodal distribution pattern of aggregate consistent with a single scattering species was found. Our results confirm that an increase of temperature induces micellar growth and that clustering of micelles occurs as the temperature approaches the cloud point. It was observed that, with increasing temperature, the higher the n-dodecyl-hexaethylene-glycol content the greater the micellar growth. The presence of sugar surfactant monomers in the mixed micelle enhances the cloud point of the system. This phase behavior is sensitive to the presence of NaCl in the micellar solution which induces cloud point depression. For a certain system composition, the cloud point decreases as the alkyl chain length of the sugar-based surfactant increases. Cloud-point thermodynamics were evaluated assuming that clouding indicates the solubility limit when phase separation occurs. The micelle–solvent interactions were characterized from the compensation temperatures, which were determined from the enthalpy–entropy plots.
Keywords: Micelas; Mixed micelles; Micellar size; Cloud point; n-Dodecyl-β-d-maltoside; n-Decyl-β-d-maltoside; n-Dodecyl-hexaethylene-glycol